Competence and Professional Skills in Training Future Specialists in the Field of Physical Education and Sports - Ivanii, Ihor V. (2020)
The relevance of the problem is determined by the need to understand the further strategy of improving the training of physical education and sports specialists. The purpose of the article is to study the problem of correlation between the notions of “competence” and “professional skill” in the context of the formation of a specialist in the field of physical education and sports. The study of the relationship between the notions of “competence” and “professional skill” was conducted on the basis of an array of special literature on the competent approach to training of physical education and sports specialists, including more than 200 sources published in different countries. The article analyses negative trends in the content of training future specialists in the system of higher professional physical education based on a competence approach. The acme-culturological approach for improving the professional training of future specialists is proposed and tested, the stages of formation of professional skills of future specialists in the training process are presented. There is a need to focus on the identified features of professional training of young people to professions in the field of physical education and sports. The proposed system of professional training of future specialists of physical education and sports on acme-culturological bases directs teachers to improve the quality of training graduates in their future professional activities.